VIV response of risers with large aspect ratio and low rigidity using a numerical scheme based on wake oscillator model. (January 2022) - Prethiv Kumar, R.; Nallayarasu, S.
Abstract: The crossflow (CF) response of a flexible riser subjected to vortex-induced vibration (VIV) has been carried out using numerical simulation based on wake oscillator model for different aspect ratio ( L/D ), flexural rigidity ( EI ), mass ratio ( μ ), and the axial tension (Θ). Experiments were conducted on a scale model with a shear flow profile. The numerical model has been validated by comparing it with VIV responses obtained from experiments for shear flow profile. Parametric studies have been performed using the numerical model to obtain the crossflow root-mean-square ( RMS) displacement along the length for L/D range of 100 to 3000, the flexural rigidity of 50 to 2870 MPa, mass ratio of 1.955 to 10, and axial tension of 0 to 3000 N for uniform flow profile. The results of the shear flow profile were presented with those obtained from equivalent uniform flow (equivalent mean velocity). The VIV response indicates that the standing wave pattern occurs for L/D  < 1500. In contrast, the travelling wave pattern was observed for L/D  = 3000 and indicated the wave pattern is mixed for a transition range of L/D  = 1500. It was also observed that the response mode is highly dependent on L/D, EI, and shear flow profile during independent on mass ratio. The VIV displacement response of flexible risers with helical wires reduces by 90% compared with riser without helical wire for a riser diameter to wire diameter ratio of 10 and pitch to riser diameter ratio of 8 in uniform flow.